Indo-Pacific: An evolving concept affecting regional order? - Bastos, Rita Alexandra Simas (2022)
The Indo-Pacific concept has been gaining attention in the international dynamics of Asia. Endogenous and exogenous countries and international organizations – Japan, India, ASEAN, the United States, the European Union and China – have shared their perspectives of the Indo-Pacific region. These could change the regional power dynamics. The case of the EU’s participation is peculiar, given its’ distance from the dynamics. China is vital for this study as a top regional player and her reception of the concepts. Our research goals consisted of determining if the Indo-Pacific concept is changing the relationships between the actors of the region and in what ways that is occurring. It was also our interest to discover each perspective's origins and particularities. Our main research question was Is the Indo-Pacific changing the relationships between the powers of this region?, followed by minor questions regarding the European Union and its own perspective of the region as an exogenous power and China’s reception of the perspectives. A literature review was conducted to assess the state of the art of the Indo-Pacific studies, and an inductive content analysis was executed to texts of every actor aforementioned. We concluded that the points of convergence found in the concepts create surprising alignments between actors and shift how the areas of cooperation are dealt with at the international level.